Prenatal diagnosis of hypoplastic left heart syndrome with PAPVC and FO restriction and pulmonary hypertension – coexisting factors suggesting poor prognosis due to pulmonary hypertension with histopathological confirmation - Nowakowska, Aleksandra; Krekora, Michał; Talar, Tomasz; Kopala, Marek; Romanowicz, Hanna; Respondek-Liberska, Maria (Prenatal Cardiology, 2022)
Prenatal hypoplastic left heart syndrome (HLHS) is widely described in the literature as a congenital heart defect with underdevelopment of the left side of the heart. There are many well-known risk factors that comprise a poor prognosis, such as coexisting genetic syndrome, or extra-cardiac malformations like diaphragmatic hernia, premature delivery, low birth weight, etc. Herein we present an isolated case of HLHS, with echocardiographic data from the third trimester, after in utero transfer, born at term in a tertiary centre with an obstetrics, cardiology, and cardiac surgery department within the same research institute, with Prostin administration without delay, Norwood procedure planned relatively early, but despite all efforts – neonatal demise. We believe that the main cause of death was pulmonary hypertension, and such an observation was never published before.